Memórias (in)visíveis: narrativas de velhos sobre suas infâncias em Belém do Pará (1900 - 1950) - DUARTE, Antonio Valdir Monteiro (2008)
This research looks into the infancy in the city of Belém of Pará state, in the first half of the last century (1900 1950). The intention is to understand the reality of the children who lived in an epoch full of great transformations in the economic, political, social and cultural levels. The city of Belém lived, at that time, one of the most prosperous moments of its history, due to the large rubber production, which posed, until the end of the XIX century, as one of the most commercialized and exported products of the country. This way, the study aimed at understanding the historical context, especially, in the first half of the XX century. The rubber apogee led the city to a surprising development, being even compared to the big European cities. However, all the modernizing project carried out in the city brought consequences and contradictions, which were made worse by the decreasing of the rubber economy, contributing considerably to the differences between the emerging elite, which made use of all the services offered in the city, and the less favored class, that was kept aside of all the process. In this scenario, we meet the child who started to be seen as a subject of rights. Nevertheless, little was done to guarantee that those rights would be respected. In order to understand the infancy in this period, narratives were taken from the elderly ones who were selected accordingly to the following criteria: They should be aged from 80 yrs. Old, have lived their childhood in the city of Belém, have both physical and psychological conditions to remember and narrate their infancies. The narratives were decisive to understand, for example, aspects of the familiar composition that, at the time, were characterized by respect, obedience and, above all, by the imposition; the relationship of the child with the public space; the arrival of the child to the school to study, despite the difficulties imposed by a under formation system; the alternatives of leisure found by the child, the politics of assistance to the abandoned child; among others. Besides authors who discuss and carry out research upon the oral history such as Thompson, Alberti, Bosi, Vidal, we dialog with others from the area of the infancy such as Kramer, Tozoni-Reis, Demartini, Rizzini, Arriés, and, also in the area of historiography and Amazon history such as Sarges, Figueiredo, Salles, Mendes, among others. Finally, the research preferred narratives which, in constant dialog with the theoretical references, were the lead thread of the construction of the history of the infancy in the city of Belém.